A hybrid algorithm for recognizing pathology of the retina from an image using neural network modeling. - Badalova Maftuna Shukhratovna (Periodica Journal, 2022)
This paper presents studies of the method for determining the pathology of the retina by neural network modeling
Keywords: network; modeling; algorithm; retina